Esclerose sistêmica difusa com hipertensão pulmonar isolada: relato de caso - Zanati, Silméia Garcia [UNESP]; Okoshi, Katashi [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Inoue, Roberto Minoru Tani [UNESP]; Okoshi, Marina Politi [UNESP] (Sociedade Brasileira de Pneumologia e Tisiologia, 2000)
Systemic sclerosis (SS) is an uncommon disease characterized by small blood vessel vasculopathy and increased connective tissue in the skin and in other organs. The pulmonary involvement is common in SS; however, pulmonary hypertension without interstitial fibrosis is rare. The authors present a case of the diffuse form of SS with isolated pulmonary hypertension. The diagnosis of pulmonary hypertension was suggested by physical examination and confirmed by doppler-echocardiography which allowed for the estimation of the pulmonary artery systolic pressure in 80 mmHg. The authors started treatment with nifedipine; however, as the patient presented side effects, it was not possible to increase the dose beyond 30 mg/day. In this dosage, nifedipine did not decrease the pulmonary arterial pressure.

A esclerose sistêmica (ES) é uma doença incomum, caracterizada por alterações vasculares e fibrose em pele e vários órgãos. O envolvimento pulmonar é freqüente na ES; entretanto, hipertensão pulmonar (HP) na ausência de fibrose intersticial é raramente observada. Os autores descrevem um caso de ES difusa com HP isolada em paciente do sexo feminino, de 49 anos. O diagnóstico de HP pôde ser sugerido pelo exame físico e confirmado por ecodopplercardiograma, que permitiu estimar a pressão sistólica em artéria pulmonar em 80mmHg. Tratamento foi iniciado com nifedipina; entretanto, devido a efeitos colaterais da droga, não foi possível o aumento da dose além de 30mg ao dia; nesta dosagem, a nifedipina não acarretou redução da pressão arterial pulmonar.
Diffuse systemic sclerosis with isolated pulmonary hypertension: a case report
Keywords: Systemic scleroderma; Nifedipine; Pulmonary hypertension; Vasodilatador agents; Doppler echocardiography; Escleroderma sistêmico; Nifedipina; Ecodopplercardiograma; Hipertensão pulmonar; Vasodilatadores; Ecocardiografia doppler